De-biasing strategic communication - Tobias Gesche (University of Zurich, Department of Economics, 2021)
This paper studies the effect of disclosing conflicts of interest on strategic communication when the sender has lying costs. I present a simple economic mechanism under which such disclosure often leads to more informative and, at the same time, also to more biased messages. This benefits rational receivers but exerts a negative externality from them on naive or delegating receivers. Disclosure is thus not a Pareto-improvement among receivers. I identify general conditions of the information structure under which this effect manifests and show that whenever it does, full disclosure is socially inefficient. These results hold independently of the degree of the receivers' risk-aversion and for an arbitrary precision of the disclosure statement.
Keywords: D82; D83; L51; 330; Strategic communication; misreporting; conflict of interest; disclosure; Kommunikationsstrategie; Interessenkonflikt; Informationspflicht; externer Effekt